A practical compendium on advances in plant breeding - Osman, Mohamad (Persatuan Genetik Malaysia, 2014)
Plant breeding has always played an important role in plantation and agriculture research, especially for ensuring food security, by developing new varieties that are high yielding, resistant to pests and diseases, drought-resistant and adapted to different environments and growing conditions.